New MT(2) Melatonin Receptor-Selective Ligands: Agonists and Partial Agonists - Boutin, Jean A. (Int J Mol Sci, 2017)
The search for melatonin receptor agonists and antagonists specific towards one of the receptor subtypes will extend our understanding of the role of this system in relaying circadian information to the body. A series of compounds derived from a hit compound discovered in a screening process led to powerful agonists specific for one of the isoform of the melatonin receptor namely, MT(2). The compounds are based on a poorly explored skeleton in the molecular pharmacology of melatonin. By changing the steric hindrance of one substituent (i.e., from a hydrogen atom to a tributylstannyl group), we identified a possible partial agonist that could lead to antagonist analogues. The functionalities of these compounds were measured with a series of assays, including the binding of GTPγS, the inhibition of the cyclic AMP production, the β-arrestin recruitment, and the cell shape changes as determined by cellular dielectric spectroscopy (CellKey(®)). The variations between the compounds are discussed.